The Preferred Leadership Styles of Principals as Perceived by Teachers who Received Queen Rania ALAbdullah Award for Excellent Teacher and their Relation to Educational Excellence of those Teachers - Abu-Tineh, Abdullah; Al Rosan, Esmat (Jordan Journal of Educational Sciences, 2008)
The purpose of this study was to identify the preferred leadership styles of principals as perceived by teachers who received Queen Rania AL- Abdullah Award for Excellent Teacher and their relation to educational excellence of those teachers. The sample for this study consisted of 62 teachers who received Queen Rania Al- Abdullah Award for Excellent Teacher in the academic year 2006/2007. Results of the study showed a strong, positive, and significant relationship (r=.706) between transformational leadership style and educational excellence. Moreover, results showed a moderate, positive, and significant relationship (r= .501) between transactional leadership style and educational excellence. However, there was a weak, negative, and insignificant relationship (r=-.124) between laissez-faire leadership style and educational excellence. Furthermore, results indicated that transformational leadership was the best predictor of educational excellence (.489) followed by transactional leadership (.084). However, laissez-faire leadership was found to be negative and insignificant predictor of educational excellence